Facilitators of Skilled Birth Attendants’ Utilization in Government and Christian Health Association of Malawi Hospitals: A Cross-Section Study of Lilongwe Rural - Sumani, Woneckilly Kuseni; Makwero, Christopher (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Background: Every woman must have access to a Skilled Birth Attendant (SBA) for routine care and management of complications during labour, childbirth, and early postnatal period. SBA utilization has been identified as an essential approach of reducing maternal morbidity and mortality among reproductive age group of 15-49. Malawi as a developing country is also utilizing skilled birth attendants in an effort to reduce maternal death by 70 per 100,000 births. Report of 2020 from Demographic and Health Survey (DHS) on skilled birth attendants (SBA) revealed that Malawi was 89.8% by 2018, while Lilongwe District, the study area, was 67% of SBA utilization against a target of skilled birth attendant utilization of 95% by the year 2022. Purpose: To evaluate the facilitators of skilled birth attendants’ utilization in government and CHAM hospitals and their relationship to hospital delivery. Methods: This research used logistic regression test and quantitative cross-sectional approach. Questionnaires were used to collect data from December 2021 to February 2022 in 390 participants. The sampling techniques used were cluster and random sampling. Results: Based on logistic regression marital status (p=0.001, OR 14.56), pregnancy complication (p=0.000, OR 12.21), and ANC three times (p=0.010, OR 2.11) and four times (p=0.000 OR 0.76) were found to be significantly associated with hospital delivery. On the other hand ANC once (p=0.005, OR -2.33) and twice (P=0.008, OR -1.94) did not significantly influence utilization skilled birth attendants by pregnant mothers Conclusion: Based on the results, it is concluded that age from 15 to 30 and employment, marital status, education, complication, antenatal clinic, are the facilitators for pregnant mothers to utilize skilled birth attendant. These facilitators might be of importance for policy makers to consider when coming up with programs to increase skilled birth attendants utilization at rural area of Lilongwe District.